P505 Real-world short-term effectiveness of ustekinumab in Crohn's disease: Results from the ENEIDA Registry. (25th January 2019) - Iborra, M; Beltrán, B; Fernández, A; Gutiérrez, A; Antolín, B; Huguet, J M; de Francisco, R; Merino, O; Carpio, D; García López, S; Mesonero, F; Mínguez, M; et al.
Abstract: Background: Ustekinumab is a monoclonal antibody targeting interleukins 12 and 23. Its effectiveness in clinical practice has not yet been demonstrated. The aim of this study was to assess the real-world, short-term effectiveness of ustekinumab in medically refractory Crohn's disease (CD) (CROHNUSK study). Methods: Multi-centre study of CD patients receiving ustekinumab after June 2017 (when it was approved in Spain) and at the recommend dose (a single iv infusion of 6 mg/kg followed by a sc injection of 90 mg at Week 8). The Harvey‐Bradshaw Index (HBI) was used to evaluate clinical remission (HBI score ≤4). Values for HBI, C-reactive protein (CRP), and faecal calprotectin (FC) were recorded at baseline and at Weeks 8 and 14. Demographic and clinical data, endoscopy at baseline when available, previous treatments, adverse events (AEs), and hospitalisations were documented. Possible predictors of clinical remission were examined. Results: A total of 305 CD patients were analysed (Table 1). Characteristics of study population At baseline, 217 (72%) had an HBI score of >4 points. Of these, 101 (47%) and 126 (58%) achieved clinical remission at Weeks 8 and 14, respectively. Of the 109 patients who were on corticosteroids at baseline, 52 (48%) were in corticosteroid-free remission at Week 14. FC levels returned to normal (<250 µg/g) in 66 (22%) and 74 (24%) patients at Weeks 8 and 14, respectively. CRP returned to normal levels (<3 mg/l) in 122 (40%) and 106 (35%) patients at Week 8 and 14, respectively. HBI, FC, and CRP values over time are shown in Figure 1. HBI, FC, and CRP values over time. AEs were recorded in 12% of patients. A total of 40 patients (13%) were hospitalised, in 7 cases owing to AEs. Intolerance to the most recent anti-TNF agent and fewer previous anti-TNF agents were associated with clinical remission at Week 14. Endoscopic severity, but not previous vedolizumab treatment, was associated with poor response. Conclusions: This is the first study to show the real-world safety and effectiveness of ustekinumab in a large cohort of highly refractory CD patients.